The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4317/jced.55601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the electrochemical behaviour of Nickel-Titanium-based orthodontic wires: Effect of some natural corrosion inhibitors in comparison with fluoride

Abstract: Background The aim of this study is to assess the corrosion resistance behaviour of Nickel-Titanium-based orthodontic wires (NiTi) in different concentrations of Sodium Fluoride (NaF) and the corrosion’s inhibitory effect of the extracts of some medicinal plants (essential oils, hydrosols and extract). Material and Methods In this study we used NiTi (3M) and CuNiTi (ORMCO, 35°C, California) orthodontic wires. The following electrolytes were prepared: Lactate Ringer solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…1,32 However, some mouthwashes have been reported to cause the release of ions and decrease corrosion resistance. 34,35 This study observed that copper ion release from the CuNiTi orthodontic archwire in Group B (2% chitosan, which simulated a mouthwash) was lower than that of the control.…”
Section: Discussionmentioning
confidence: 83%
“…1,32 However, some mouthwashes have been reported to cause the release of ions and decrease corrosion resistance. 34,35 This study observed that copper ion release from the CuNiTi orthodontic archwire in Group B (2% chitosan, which simulated a mouthwash) was lower than that of the control.…”
Section: Discussionmentioning
confidence: 83%
“…NaF content in perioKin ® (CHX-NaF) mouthwash can increase the metal ions released from the CuNiTi orthodontic wire. Heravi et al found that the NaF content in mouthwash solution would decrease the corrosion resistance of NiTi and CuNiTi wires as the NaF concentration increased (Heravi, Hadi Moayed and Mokhber, 2015;Fatene et al, 2019). Sabah and Jarjees also reported that the interaction between fluoride and titanium might cause destruction to the metal coating of the archwires and degrade the mechanical properties (Sabah, Jarjees and Awni, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…HF degrades the protective oxide layers on the surface, which leads to corrosion (Castro et al, 2015;Hafez et al, 2011;Lü et al, 2009;Marques et al, 2012;Suárez et al, 2010). But there are several published studies on the corrosion resistance of NiTi alloys in saliva and NaF solutions even with increasing concentrations of fluorides (Heravi, Hadi Moayed and Mokhber, 2015;Mirhashemi, Jahangiri and Kharrazifard, 2018;Fatene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…HF degrades the protective oxide layers on the surface, which leads to corrosion (Castro et al, 2015;Hafez et al, 2011;Lü et al, 2009;Marques et al, 2012;Suárez et al, 2010). But there are several published studies on the corrosion resistance of NiTi alloys in saliva and NaF solutions even with increasing concentrations of fluorides (Heravi, Hadi Moayed and Mokhber, 2015;Mirhashemi, Jahangiri and Kharrazifard, 2018;Fatene et al, 2019).…”
Section: Introductionmentioning
confidence: 99%